Economic growth among tiger cub countries / Erna Sharida Putek ... [et al.] - Putek, Erna Sharida; Azmi, Siti Nurul Ashykin; Ramli, Afifah; Abu Hassan Asari, Fadli Fizari (2013)
Gross Domestic Product (GDP) is important for the process of economic growth in many developing countries. In the South East Asian region, a magical growth of GDP in 1980s and 1990s for countries known as tiger cub countries has impressed the world. The question is - Will the same sustainable growth appear in the next decade? Therefore, this study is designed to investigate which factor is the most dominant in catalysing the economic growth among these tiger cub countries. Several factors such as government initiative, economic liberalisation and international investment have been analysed. A set of panel data for a 20 year period (1990-2009), which consists of data from Malaysia, Indonesia, Philippines and Thailand was used. Based on the POLS estimation, the results successfully highlighted the dominance of the government initiative. The higher the expenditure, the more improved it will be in the context of economic growth. For future studies, it is proposed to have more emerging South East Asian countries such as Vietnam and Myanmar due to their potential to become the next tiger cub countries.